Altered Cellular Distribution and Sub-Cellular Sorting of Doppel (Dpl) Protein in Human Astrocytoma Cell Lines - Elena Sbalchiero; Alberto Azzalin; Silvia Palumbo; Giulia Barbieri; Agustina Arias; Luca Simonelli; Luca Ferretti; Sergio Comincini (Cellular Oncology)
Doppel, a prion-like protein, is a GPI-membrane anchored protein generally not expressed in the Central Nervous System (CNS) of different mammalian species, including human. Nevertheless, in astrocytomas, a particular kind of glial tumors, the doppel encoding gene (PRND) is over-expressed and the corresponding protein product (Dpl) is ectopically localized in the cytoplasm of the tumor cells. In this study we have analysed the sub-cellular localization of Dpl using double-immunofluorescence staining and confocal microscopy examinations in two astrocytoma-derived human cell lines (IPDDC-A2 and D384-MG). Our results confirmed that Dpl is localized in the cytoplasm of the astrocytoma cells and indicated that it is mostly associated with Lamp-1 and Limp-2 positive lysosomal vesicles and, marginally, to the Golgi apparatus and other cellular organelles. Noticeably, none of the examined tumor cells showed a membrane-Dpl localization. The membrane-associated Dpl expression was restored after the transfection of the astrocytoma cells with mutated Dpl-expression vectors in its glycosylation sites. Additionally, Dpl showed altered expression and traffic using the acidotropic agent ammonium chloride, leading to the accumulation of Dpl in nascent exocytic vesicles. Altogether, these results indicated that in the astrocytic tumor cells Dpl has an altered biosynthetic trafficking, likely derived from abnormal post-translational processes: these modifications do not permit the localization of Dpl in correspondence of the plasma membrane and lead to its intracellular accumulation in the lysosomes. In these proteolytic compartments, the astrocytic tumor cells might provide to the degradation of the excess of a potentially cytotoxic Dpl product.